Place navigation in rats is impaired by lesions of medial septum and diagonal band but not nucleus basalis magnocellularis. - Hagan, J; Salamone, J; Simpson, J; Iversen, S; Morris, R (1988)
The role of forebrain cholinergic projections in place navigation learning was assessed in two experiments. Following surgery, rats were required to learn the spatial location of an underwater platform on the basis of distal room cues. Bilateral injections of ibotenic acid into the nucleus basalis magnocellularis depleted choline acetyltransferase (ChAT) from the anterior and temporoparietal cortex but not the hippocampus. Separate histological studies confirmed the accuracy of the lesions and demonstrated a marked loss of cortical acetylcholinesterase. These rats subsequently showed no deficits in spatial learning or memory. In a second experiment, bilateral lesions of the vertical limb of the diagonal band of Broca and medial septum depleted ChAT from the hippocampus and posterior cortex but not the anterior cortex. Histological studies confirmed the accuracy of the lesion and showed a pronounced loss of acetylcholinesterase from the hippocampus. These rats were deficient in spatial learning and showed reduced spatial bias during transfer tests. The data are discussed in the light of the hypothesis that the cholinergic innervation of the hippocampus plays a key role in spatial reference memory processes involved in place navigation.